Arterial Stiffness Is Associated with Peripheral Sensory Neuropathy in Diabetes Patients in Ghana - Kwame Yeboah; Jennifer A. Agyekum; Richard N. A. Owusu Mensah; Patrick K. Affrim; Linda Adu-Gyamfi; Rita O. Doughan; Afua B. Adjei (Journal of Diabetes Research)
Objective. Peripheral sensory neuropathy (PSN) is among microvascular complications of diabetes that make patients prone to ulceration and amputation. Arterial stiffness is a predictor of cardiovascular diseases and microvascular complications associated with diabetes. We investigated the association between PSN and arterial stiffness, measured as aortic pulse wave velocity (PWVao) and cardio-ankle vascular index (CAVI). Method. In a case-control design, arterial stiffness was measured in 240 diabetes patients and 110 nondiabetic control. Large-fibre nerve function was assessed by vibration perception threshold (VPT) using a neurothesiometer. PSN was defined as the VPT > 97.5th percentile from age- and gender-adjusted models in nondiabetic controls. Results. The overall prevalence of PSN was 16.6% in the entire study participants. Compared to non-PSN participants, PSN patients had higher levels of PWVao (9.5 ± 1.7 versus 8.7 ± 1.2 m/s, p=0.016) and CAVI (8.4 ± 1.3 versus 7.6 ± 1.1, p=0.001). In multiple regression models, VPT was associated with PWVao (β=0.14, p=0.025) and CAVI (β=0.12, p=0.04). PSN patients had increased odds of CAVI (OR = 1.51 (1.02–2.4), p=0.043), but not PWVao (OR = 1.25 (0.91–1.71), p=0.173). Conclusion. PWVao and CAVI were associated with VPT and PSN in diabetes patients in Ghana. Patients having PSN have increased odds of CAVI, independent of other conventional risk factors.